Respiration, reactive oxygen species and uncoupling proteins - Brand, Martin (Henry Stewart Talks, 2007)
Reactive oxygen species production by mitochondria, Mitochondrial free radicals and ageing in short-lived and long-lived species, Topology and sites of ROS production in the electron transport chain, Regulation of ROS production by mild uncoupling, Uncoupling of mitochondria by uncoupling proteins, Superoxide and reactive alkenal activation of UCPs, A model for UCP activation, Evidence that UCPs attenuate ROS
Reviewed at 2016/11/18, Archived at 2022/03/22